Research on Circular Economy and Sustainable Entrepreneurship Based on Bibliometric Study - Judijanto, Loso; Tomasoa, Sefnat Kristianto; Widiarta, I Putu Gede Didik; Harsono, Iwan; Asniar, Nunut (Westscience Press, 2025)
This bibliometric analysis investigates the expansive domains of circular economy (CE) and sustainable entrepreneurship, focusing on their evolution and interlinkage within academic literature from 2000 to 2025. By leveraging data from Scopus and employing VOSviewer for visual mapping, the study identifies core themes such as innovation, sustainable development, and business model innovation, highlighting their prevalence and evolution over time. The analysis underscores the centrality of CE and sustainable entrepreneurship in fostering environmental sustainability and economic growth. Key findings indicate a strong emphasis on eco-innovation and the integration of corporate social responsibility into competitive business strategies. Despite significant advancements, the research landscape exhibits gaps, particularly in addressing socio-economic barriers and the full integration of social aspects within CE practices. The study not only maps the current intellectual terrain but also suggests future research directions aimed at addressing these gaps and enhancing the practical application of CE principles across different economic contexts.